PERAN ZAKAT DALAM MENGURANGI KEMISKINAN DI INDONESIA (STUDI KASUS: PROGRAM BEASANTRI YANG DISELENGGARAKAN OLEH BAZNAS KABUPATEN PURWAKARTA) - Danarsetyo Rahmadian Murti; Desta Tri Andini; Felicia Zein; Abdul Fadhil (Cahaya Ilmu Bangsa Institute, 2024)
The Bea Santri program organized by BAZNAS Purwakarta Regency is one of the efforts to optimize productive zakat in the education sector. This program provides monthly pocket money assistance to santri from underprivileged families, with the aim of easing the economic burden on mustahik families while increasing santri's learning motivation. This study evaluates the effectiveness of the program in supporting education and its contribution to mustahik welfare through qualitative and quantitative approaches. The results show that the program is effective in improving access to education, academic achievement, and students' opportunities to become agents of change in their communities. In addition, there is a positive impact on the economic welfare of mustahik families, especially in reducing the burden of education costs. However, challenges such as limited program coverage and long-term monitoring mechanisms still need to be improved. To optimize this program, it is recommended to improve zakat collection through technological innovation, reporting transparency, and collaboration with other stakeholders. With these steps, the Bea Santri Program can become a successful model of productive zakat management in Indonesia.